Pengaruh Media Video Animasi Berbasis Powtoon Terhadap Minat dan Hasil Belajar PPKn pada Siswa Kelas IV SD Negeri 77 Bengkulu - Nurlaila; Widi Winarni, Endang; Parmadi, Bambang (UNIB Press, 2025)
This research aims to analyze the influence of Powtoon-based animated video media on interest and learning outcomes in PPKn in class IV students at SD Negeri 77 Bengkulu. This research is a quasi-experimental research with a quantitative approach. The data collection techniques used are tests, questionnaires and documentation. The instruments used in this research were pretest and posttest sheets, questionnaire sheets. The collected data was then analyzed quantitatively using SPSS. The results of the research show that through cartoon-based animated video media it can have an influence on interest and learning outcomes. The conclusion of this research is that the Ho hypothesis is rejected and Ha is accepted, meaning that there is a significant influence of Powtoon-based animated video media on interest and learning outcomes.